2023
DOI: 10.1093/dote/doad034
|View full text |Cite
|
Sign up to set email alerts
|

Performance of radiomics-based artificial intelligence systems in the diagnosis and prediction of treatment response and survival in esophageal cancer: a systematic review and meta-analysis of diagnostic accuracy

Abstract: Summary Radiomics can interpret radiological images with more detail and in less time compared to the human eye. Some challenges in managing esophageal cancer can be addressed by incorporating radiomics into image interpretation, treatment planning, and predicting response and survival. This systematic review and meta-analysis provides a summary of the evidence of radiomics in esophageal cancer. The systematic review was carried out using Pubmed, MEDLINE, and Ovid EMBASE databases—articles descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated using deep learning-based or radiomics-based methods to analyze contrast-enhanced CT images can preoperatively predict pCR of ESCC [6]. Nevertheless, the majority of studies primarily concentrate on single time-point CT images (pre- or post-treatment), neglecting the temporal dynamics and alterations which can be elucidated through longitudinal contrast-enhanced CT images [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated using deep learning-based or radiomics-based methods to analyze contrast-enhanced CT images can preoperatively predict pCR of ESCC [6]. Nevertheless, the majority of studies primarily concentrate on single time-point CT images (pre- or post-treatment), neglecting the temporal dynamics and alterations which can be elucidated through longitudinal contrast-enhanced CT images [7].…”
Section: Introductionmentioning
confidence: 99%